The Influence of High School Students' Character Education Program on Increasing Competency Readiness to Face Future Challenges - Salma Rahma; Imanuela Paskha Christianto; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to explore and understand the various methods implemented by educational institutions to improve students' character skills. With increasing awareness of the value of character education in developing well-rounded individuals who are ready for the future, the literature review article uses publications from 2021-2025 that can be accessed via Google Scholar. A literature review was conducted to identify relevant studies. Key traits consistently targeted for development include resilience, self-confidence, drive, self-esteem, and social values such as respect, tolerance, and caring. This character development strategy is implemented through three main channels: the formal curriculum, extracurricular activities, and through the creation of a supportive school environment and culture. Factors identified as determinants of success include strong and committed school leadership, comprehensive engagement of all staff, active student participation, and strong collaboration with parents and the community. In conclusion, effective character development requires a planned, deliberate strategy tailored to the specific context of each school, with the ultimate goal of improving student well-being and preparing them for life after school.